CONTENT ANALYSIS OF “PATHWAY TO ENGLISH” AN ENGLISH TEXTBOOK USED IN CLASS X-3 AT SMA PAWYATAN DAHA KEDIRI PUBLISHED BY ERLANGGA RELEVANCY TO CURRICULUM 2013 - Bintoro, Muhamad (Universitas Nusantara PGRI Kediri, 2019)
This research is done based on the writer research and experience that text book holds an important role in teaching and learning process. Text book contains the explanation of the material, excercises and evaluation which may deepen the students’ understanding about certain t opic. That’s why the use of text book will be very crucial in teaching and learning process. The problem faced nowadays is that not all published text book relevant to curriculum, moreover next several years all schools in Indonesia are required to use curriculum 2013. In this research, the writer analyses “Pathway to English” an English text book used in class X-3 at SMA Pawyatan Daha Kediri Published by Erlangga with the purpose to find out whether or not it relevants to curriculum 2013. Since this research is qualitative research whose purpose is to find out the relevancy of a text book to curriculum 2013, the writer uses content analysis approach to analyse the content of the workbook. The object of the research is “Pathway to English” an English Textbook Used in Class X-3 at SMA Pawyatan Daha Kediri Published by Erlangga. To get the data the writer doccumentation checklist based on KEMENDIKBUD’s. Conclusion of the research is “Pathway to English” an English Textbook Used in Class X-3 at SMA Pawyatan Daha Kediri Published by Erlangga is approximately relevant to curriculum 2013 and can be used as a learning source in teaching learning process in the classroom. This text book is very well organized, interesting and consists of all material students should learn in a year. This book will be very helpful in teaching learning process. Based on the result and conclusion the writer suggest to; 1) teacher should provide another learning sources to make the students become more active, 2) provide any audio or video to support material in this text book, 3) create summative test for each chapter to strengthen students’ understanding towards the material they have learned.